Papers - Copper, Brass and Bronze - Comparative Properties of Oxygen-free High Conductivity, Phosphorized and Tough-pitch Coppers (With Discussion) - W. R. Webster; J. L. Christie; R. S. Pratt (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1933)
Since the delivery of our paper on Some Comparative Properties of Tough-pitch and Phosphorized Copper,1 a new brand known as "oxygen-free high-conductivity copper" (brand OFHC) has become available to consumers. It was thought desirable to make a comparison between the properties of this material and those of the materials covered by our original paper and its discussion. Preliminary tests had indicated some notable differences. A billet of oxygen-free high-conductivity copper was taken from regular production. A chemical analysis of the particular billet was not made, but the producer of the material has given as typical the analysis shown in Table 1. The